2019
DOI: 10.3791/59997
|View full text |Cite
|
Sign up to set email alerts
|

Using Human Induced Pluripotent Stem Cells for the Generation of Tumor Antigen-specific T Cells

Abstract: The generation and expansion of functional T cells in vitro can lead to a broad range of clinical applications. One such use is for the treatment of patients with advanced cancer. Adoptive T cell transfer (ACT) of highly enriched tumor antigen-specific T cells has been shown to cause durable regression of metastatic cancer in some patients. However, during expansion, these cells may become exhausted or senescent, limiting their effector function and persistence in vivo. Induced pluripotent stem cell (iPSC) tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, at the time of this study there was no published work indicating whether hBM-MSCs can induce hematopoiesis of hiPSC similar to OP9 cells. Based on our experience of using the classical OP9 co-culture system (Good et al, 2019), we reasoned that the gradual loss of stem cell properties in hBM-MSCs during expansion may be detrimental. Therefore, we limited the expansion of hBM-MSCs to 4-5 passages prior to Hp-spheroid formation (Sabatino et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, at the time of this study there was no published work indicating whether hBM-MSCs can induce hematopoiesis of hiPSC similar to OP9 cells. Based on our experience of using the classical OP9 co-culture system (Good et al, 2019), we reasoned that the gradual loss of stem cell properties in hBM-MSCs during expansion may be detrimental. Therefore, we limited the expansion of hBM-MSCs to 4-5 passages prior to Hp-spheroid formation (Sabatino et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that iPSCs are a potent tool for generating and developing T-cell lineages in vitro. This advancement holds great potential in the field of regenerative medicine, particularly for the progress of allogeneic therapies [37].…”
Section: Generationmentioning
confidence: 99%
“…Typically, only one third of the wells contain a single cell when starting with a concentration of 0.5 cells per aliquot ( 18 ). Micromanipulation is another technique developed mainly to isolate embryos or stem cells, but it could be applied to T cells, particularly since the potential of generating human induced pluripotent stem cells to differentiate into anti-tumor T cells has been explore ( 19 ). A microscope-guided capillary pipette is used to pick single cells from a suspension culture ( 20 ).…”
Section: Single-cell Tcr and Transcriptome Sequencingmentioning
confidence: 99%